Long-term Efficacy and Safety of Sodium Oxybate in Treating Alcohol Use Disorder: A Systematic Review and Meta-Analysis - Biso, Letizia; Spini, Andrea; Petragnano, Francesco; Maggio, Roberto; Scarselli, Marco; Carli, Marco (Current Neuropharmacology, 2025)
BackgroundWorldwide, three million deaths each year are reported due to the harmful use of alcohol. To date, only a few drugs have been approved for the treatment of Alcohol Use Disorder (AUD). This systematic review and meta-analysis aim to assess the long-term efficacy and safety of sodium oxybate (SMO) treatment in patients with AUD.MethodsWe followed the PRISMA statement guidelines and searched PubMed and ISI Web of Science to retrieve the studies of interest. In total, 13 studies on long-term (>12 weeks) SMO administration in patients with AUD were included in this systematic review, and 7 were included in the meta-analysis.ResultsOverall, the abstinence rate after 12 weeks of treatment was similar in the SMO and placebo groups, while it was significantly in favour of SMO compared to Naltrexone (NTX). The completion rate was similar in all three conditions. Mean corpuscular volume (MCV) levels favoured SMO over NTX, while Alcohol Craving Scale (ACS) scores did not favour SMO. The incidence of adverse reactions varied widely between studies.ConclusionSMO in the chronic treatment of patients with AUD showed no superiority to placebo in our analysis of published RCTs, although many observational studies reported its beneficial effect in the long term. On the contrary, SMO was superior to NTX treatment on abstinence. The rate of study completion was similar in the three groups. Safety was not an issue in any of the studies included. Further studies are needed to better assess SMO efficacy and safety in the long term.
Keywords: alcohol use disorder